Simulations Based on Representative 24-h Recall Data Predict Region-Specific Differences in Adequacy of Vitamin A Intake among Cameroonian Women and Young Children Following Large-Scale Fortification of Vegetable Oil and Other Potential Food Vehicles. Issue 11 (10th September 2014) - Engle-Stone, Reina; Nankap, Martin; Ndjebayi, Alex O.; Brown, Kenneth H.
Abstract: Background: The WHO recommends assessing food and nutrient intakes to design food-fortification programs, but nationally representative dietary data are seldom available in low-income countries. Objective: Prior to initiation of food fortification in Cameroon, we measured intake of vitamin A (VA) and fortifiable foods (vegetable oil, sugar, wheat flour, and bouillon cube) to simulate the effects of fortification with different foods and VA amounts on prevalence of inadequate and excessive VA intake. Methods: Twenty-four-hour recalls were conducted among 912 women and 883 children (with duplicates in a subset) in a nationally representative cluster survey stratified by region (North, South, Yaoundé/Douala). Usual intake distributions were estimated by the National Cancer Institute method. Results: Nationally, 53% of women had a usual intake of <500 μg retinol activity equivalents/d, and 59% of nonbreastfeeding children had an intake of <210 μg retinol activity equivalents/d, although VA intake varied by region. The current fortification program (12 mg/kg VA in oil) would decrease the prevalence of inadequate intakes to 35% among both women and children, without increasing the proportion with retinol intakes >3000 μg/d among women or >600 μg/d among children. However, inadequate VA intake would remain >50% in the North, where VA deficiency was most common. Increasing VA in oil or fortifying a second food (sugar, wheat flour, or bouillon cube) would further decrease the prevalence of inadequate intakes, but, depending on the food vehicle and region, would also increase the prevalence of retinol intakes above the tolerable upper intake level, mainly among children. Conclusions: The current food-fortification program can be expected to improve dietary VA adequacy without increasing the risk of excessive intake among women and children in Cameroon. Modifications to the program must balance the potential to further increase VA intake with the risk of excessive intake among children.